The eight mountains [videorecording (DVD)] - Groeningen, Felix van; Vandermeersch, Charlotte; Norgren, Daniel, 1983-; Marinelli, Luca; Borghi, Alessandro, 1986-; Timi, Filippo, 1974-; Lietti, Elena; Mazzullo, Elisabetta; Barbiero, Lupo; Sassella, Cristiano; Palma, Andrea; Panta, Surakshya; et al. (Janus contemporaries., 2023)
An epic journey of friendship and self-discovery set in the Italian Alps, The Eight Mountains is a cinematic experience as intimate as it is monumental. Adapting an award-winning novel by Paolo Cognetti, Felix van Groeningen and Charlotte Vandermeersch portray, through observant detail and stunning landscape photography, the profound relationship between Pietro and Bruno, who first meet as children in an Alpine village. Years later, the estranged friends reunite, after the passing of Pietro's father, to realize his dream of rebuilding a ruined cabin on a mountain slope. This emotional project, and their subsequent explorations of the mountains, create a strong bond between the two individual dreams and the demands of society, ultimately driving them to pursue irrevocably divergent paths.